Changes in digoxin pharmacokinetics associated with hepatic P‐glycoprotein upregulation in rats with non‐alcoholic fatty liver disease. (21st May 2021) - Jeong, Hee Jin; Lee, Song Hee; Kang, Hee Eun
Abstract: Background & Objectives : Upregulation of hepatic P‐glycoprotein (P‐gp) expression has been reported in patients with non‐alcoholic fatty liver disease (NAFLD) and rodent models thereof. Here, we explored the changes hepatic P‐gp expression and activity in a NAFLD rat model and the effects thereof on the pharmacokinetics of digoxin (a probe substrate of P‐gp). Methods : Rats were fed a 1% (w/w) orotic acid‐containing diet for 20 days to induce NAFLD; control rats received a normal diet. P‐gp expression and biliary digoxin excretion were examined. The pharmacokinetics of digoxin were evaluated after it had been administered intravenously (10 μg·kg −1 ) and orally (200 μg·kg −1 ) to control and NAFLD rats. Results : The total areas under the plasma concentration‐time curves (AUCs) of digoxin after intravenous and oral administration were significantly smaller (by 39.1% and 73.0%, respectively) in NAFLD rats because of faster biliary digoxin excretion, reflecting elevations of hepatic P‐gp expression and activity. Notably, the steady‐state volume of distribution rose by 98.2%, while extent of oral bioavailability fell by 55.5% in NAFLD rats. Conclusion : This is the first study to report digoxin pharmacokinetic changes caused by hepatic P‐gp upregulation in NAFLD. Further studies are needed to explore the clinical impact of enhanced P‐gp‐mediated biliary excretion on pharmacotherapies using P‐gp substrates in patients with NAFLD.